The Production of Lightweight Aggregate for New Construction Material - Khairul Nizar Ismail, Dr. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12 June 2007 at Park Royal Hotel, Penang.